AB0814 The BEPAS Cohort: A Prospective Cohort of Psoriatic Arthritis in Belgium: Study Design and Baseline Characteristics of the 461 Recruited Patients. (9th June 2015) - de Vlam, K.; Lories, R.; Steinfeld, S.; van den Bosch, F.; Nzeusseu Toukap, A.; Malaise, M.; Taelman, V.; Van Bruwaene, F.; Vanden Berghe, M.; Joos, R.; Lenaerts, J.; Geussens, P.; et al.
Abstract : Background: Psoriatic arthritis is a chronic arthritis with major impact on the physical and psychosocial integrity of the patient. Only few prospective data are available. BEPAS (Belgian Epidemiological Psoriatic Arthritis Study) is a large prospective multicenter cohort set up in 17 Belgian rheumatology practices. Objectives: (1) to generate a comprehensive database in order to characterize the clinical presentation and the frequency of the distinct PsA subtypes; (2) to estimate the severity of disease based on disease activity scores, active inflammation and structural damage; (3) to estimate the impact in terms of health-related quality of life of PsA in Belgium and (4) to evaluate progression of structural damage in patients with PsA over time. Methods: Patients with an existing or a new clinical diagnosis of PsA and fulfilling the CASPAR classification criteria were recruited.A specific selection rule was applied to avoid selection bias. All patients gave informed consent. Recruitment of the patients occurred in 17 large rheumatology centers across Belgium. In the prospective study, patients are followed every year during the first 2 years with a possible extension for an additional 5 years. Demographics and clinical parameters, and additional information about QoL and disability were collected. X-rays of hands and feet are performed every year and axial X-rays every 2 years. Results: 461 patients (mean age: 52.79 years (±12.29), male 57%) were recruited in the 17 centers from december 2012 to July 2014. Average time between first complaints and diagnosis of PsA was 8.6 yrs (±9.3), 27.5% of the patients had a disease duration of less than 2 years. Combined peripheral and axial involvement was reported in 73.7% of the patients, only peripheral involvement in 25, 4% and only axial involvement in 0.7% of the patients. At entry polyarticular, oligoarticular and monoarticular joint involvement was reported in respectively 25.8%, 12.2% and 8.9% of the patients. Dactylitis and enthesitis were reported in respectively 11.3% and 14% at entry. Psoriasis type1 (onset <40 year) was present in 64.6%. Plaque psoriasis is the most frequent presentation (92.8%). Nail involvement was present at baseline in 39.8% of the patients. At entry the mean number of swollen joints is 2.13 (±4.53) and of tender joints is 4, 10 (±7.31). Conclusions: This large cohort paints a real-life heterogeneous presentation of PsA in Belgium. Further data collection and analysis should facilitate clinical and outcome studies in order to improve our knowledge on the impact and natural history of PsA in Belgium. Acknowledgements: This study was sponsored by MSD Disclosure of Interest: K. de Vlam Grant/research support from: MSD, R. Lories: None declared, S. Steinfeld: None declared, F. Van Den Bosch: None declared, A. Nzeusseu Toukap: None declared, M. Malaise: None declared, V. Taelman: None declared, F. Van Bruwaene: None declared, M. Vanden Berghe: None declared, R. Joos: None declared, J. Lenaerts: None declared, P. Geussens: None declared, S. Dalli'Armellina: None declared, I. Peene: None declared, G. De Brabanter: None declared, M. Van Den Berghe: None declared, J. Qu: None declared, M. Maertens: None declared, H. Leroi Employee of: MSD